Hakikat Manusia: Makhluk Jazadiyah-Ruhiyah Dan Tugas Kekhalifaan - Adiyana Adam; Radjiman Ismail; H. Moh. Natsir Mahmud (Peneliti.net, 2022)
This study aims to analyze the nature of humans as Jasadiyah-Ruhiyah creatures and the duties of the caliphate with the focus of the discussion being seen from the philosophy of Islamic education. The results showed that humans with all the completeness given by Allah SWT in the form of body and spirit will always interact with their environment. From these interactions, humans will use the hearts and minds of humans so that they will produce an action and reaction for the human itself. Human actions and reactions can be either positive or negative. This is where the role of education for humans is needed. This education will later direct humans to a thought and action whether what he does is bad or is a good thing.